Analisis Motivasi Belajar Pada Pembelajaran Daring Siswa Kelas XI Mipa 6 SMA N 1 Petarukan Pemalang - Fauziyah Isnaeni; Harto Nuroso (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This research using a questionnaire was carried out to determine the learning motivation faced by students in class XI MIPA 6 SMA N 1 PETARUKAN because knowing physics student motivation is very important in online learning. The purpose of this study was to determine: 1. How much motivation to learn physics students in online learning, 2. The role of the questionnaire in knowing the motivation to learn physics students in online learning. This research uses the type of research in the form of students filling out a link containing a learning motivation questionnaire where 35 students of class XI MIPA 6 SMA N 1 PETARUKAN are given a link in the form of a questionnaire about learning motivation in online learning. The resulting data regarding students' learning motivation was analyzed descriptively quantitatively. In this study, data showed that students' learning motivation in online learning was from each indicator, namely: 1. Knowing the desire to learn 2. Knowing the need to learn 3. Knowing the virtues of good grades 4. Knowing their own efforts in learning 5. Knowing the environment conducive learning. The average data yielded Strongly Agree 56.4% (Medium), Agree 81.4% (High), Disagree 27.4% (Low), Strongly Disagree 6% (Low). It can be concluded that the learning motivation of students in class XI MIPA 6 SMA N 1 PETARUKAN in online learning shows a moderate enthusiasm for learning.